Preparation methods of down-conversion material and photovoltaic light conversion adhesive film, and photovoltaic module
By preparing the downconversion material of Eu(TTA)3Bath europium-based complex and the photovoltaic conversion adhesive film, the electrical performance attenuation problem of crystalline silicon solar cells under high-energy ultraviolet radiation is solved, and the photoelectric conversion efficiency is improved and the ultraviolet light is effectively converted, which is suitable for photovoltaic modules.
Patent Information
- Application Number
- CN202510773955.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-15
AI Technical Summary
Crystalline silicon solar cells have ultraviolet-induced attenuation under high-energy ultraviolet radiation conditions, and existing rare earth-organic complex downconversion materials are prone to dissociation under light, resulting in a decrease in fluorescence quantum yield, limiting their industrial application in the field of photovoltaics.
Using the downconversion material of Eu(TTA)3Bath europium-based complex, the trivalent europium salt compound, TTA and Bath were dissolved in anhydrous ethanol, adjusted the pH and dried, and prepared a photovoltaic photovoltaic film, and coated it on photovoltaic glass to form an Eu(TTA)3Bath@EVA photovoltaic photovoltaic film.
It effectively reduces the ultraviolet attenuation of solar cells, improves the efficiency of solar light utilization and photoelectric conversion efficiency, and is suitable for all kinds of photovoltaic cells.
Smart Images

Figure CN120484000A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a preparation method of a down-conversion material and a photovoltaic light-conversion adhesive film, and a photovoltaic module. Background Art
[0002] The efficiency of crystalline silicon solar cells is limited by the band gap of silicon materials (E g ) and the energy of photons from ultraviolet to infrared in the solar spectrum ( hν ) is not completely matched. hν ≥E g When the battery can only use the g The excess photon energy is converted into lattice thermal energy through phonon coupling; when hν <E g When the photons are unable to excite electron-hole pairs, they are lost through transmission. Therefore, of the total energy of incident solar radiation, approximately 49% comes from low-energy photons in the near-infrared band that cannot be absorbed, while 5% of the energy loss is due to the thermal dissipation of high-energy photons in the ultraviolet band. This spectral mismatch leads to a theoretical efficiency limit of 29.4%.
[0003] Experimental studies have shown that crystalline silicon solar cells commonly experience UV-induced degradation (UVID) of their electrical performance under high-energy UV irradiation conditions. The UVID mechanism primarily involves three aspects: (1) High-energy UV photons accelerate the aging of packaging materials such as EVA and backsheets, leading to interface delamination; (2) Si-H bonds break under UV irradiation, causing a decrease in passivation performance and cell efficiency; and (3) When UV light is utilized by the cell, it generates a carrier thermalization effect. The mobility of hot carriers leads to an increase in surface defect states and severe recombination of photogenerated carriers.
[0004] Down-conversion materials can convert high-energy ultraviolet photons into low-energy visible photons. Their application in crystalline silicon solar cells not only effectively avoids UV-induced degradation but also promises to improve the cell's photoelectric conversion efficiency. Among the numerous down-conversion materials, rare earth-organic complexes have attracted considerable attention due to their advantages, including high quantum yields, large Stokes shifts, and long fluorescence lifetimes. However, in practical applications, these materials are susceptible to dissociation under illumination due to the photosensitization mechanism of the organic ligands, resulting in reduced fluorescence quantum yields and insufficient material stability. This has severely hampered their industrial application in the photovoltaic field.
[0005] Therefore, in order to solve the above technical problems, it is necessary to provide a method for preparing a down-conversion material and a photovoltaic light-converting adhesive film, and a photovoltaic module. Summary of the Invention
[0006] The purpose of the present invention is to provide a preparation method of a down-conversion material and a photovoltaic light-conversion adhesive film, and a photovoltaic module.
[0007] In order to achieve the above-mentioned purpose, the technical solution provided by one embodiment of the present invention is as follows: A method for preparing a down-conversion material, comprising the following steps: Dissolve the trivalent europium salt compound in anhydrous ethanol and stir until completely dissolved to obtain solution A; Dissolve TTA in anhydrous ethanol and stir until completely dissolved to obtain solution B; Dissolve Bath in anhydrous ethanol and heat in a water bath with stirring until completely dissolved to obtain solution C; Solution A, solution B and solution C are mixed and stirred until fully reacted, and an alkaline solution is added to adjust the pH of the solution to pH <7. The solution is filtered and dried to obtain Eu(TTA)3Bath europium-based complex down-conversion material.
[0008] In one embodiment, the trivalent europium salt compound includes at least one of EuCl 3 ·6H 2 O, EuBr 3 ·6H 2 O, and Eu(NO 3 ) 3 ·6H 2 O.
[0009] In one embodiment, the preparation of solution A includes: Dissolve 0.5 mmol~2 mmol of trivalent europium salt compound in 5 mL~20 mL of anhydrous ethanol and stir at room temperature for 10 min~30 min until completely dissolved.
[0010] In one embodiment, the preparation of solution B includes: Dissolve 1 mmol~5 mmol of TTA in 5 mL~20 mL of anhydrous ethanol and stir at room temperature for 10 min~30 min until completely dissolved.
[0011] In one embodiment, the preparation of the solution C includes: Dissolve 0.5 mmol~2 mmol of Bath in 5 mL~20 mL of anhydrous ethanol, heat in a water bath to 50℃~70℃, and stir for 10 min~30 min until completely dissolved.
[0012] In one embodiment, solution A, solution B, and solution C are mixed and stirred at room temperature for 0.5 h to 2 h to fully react, and aqueous ammonia is added to adjust the pH of the solution to pH = 6. The mixture is filtered and then dried to obtain a Eu(TTA)3Bath europium-based complex down-conversion material having a molecular structure as shown in Formula 1. [Formula 1] .
[0013] Another embodiment of the present invention provides a technical solution as follows: A method for preparing a photovoltaic light-converting adhesive film, the method comprising the following steps: Dissolve EVA powder in anhydrous ethanol and stir until completely dissolved to obtain solution D; The prepared Eu(TTA)3Bath europium-based complex down-conversion material was added to solution D and stirred until fully reacted to obtain solution E; Solution E is drop-coated on the photovoltaic glass, and then heated and cured. After ethanol is volatilized, it is cooled to form a Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film on the photovoltaic glass.
[0014] In one embodiment, the preparation of the solution D comprises: Dissolve 0.2 g~1 g of EVA powder in 5 mL~20 mL of anhydrous ethanol and stir magnetically for 10 min~30 min until completely dissolved.
[0015] In one embodiment, the preparation of the solution D comprises: Add 1 vol% to 2 vol% of Eu(TTA)3Bath europium-based complex down-transfer material to solution D and stir at room temperature for 20 min to 40 min until the reaction is fully completed.
[0016] In one embodiment, after the solution E is drop-coated on the photovoltaic glass, the curing temperature is heated to 75° C. to 95° C.
[0017] Another embodiment of the present invention provides the following technical solutions: A photovoltaic module, characterized in that the photovoltaic module includes photovoltaic glass and a photovoltaic light-converting adhesive film located on the photovoltaic glass, and the photovoltaic light-converting adhesive film is prepared using the above-mentioned preparation method.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The down-conversion material and photovoltaic light-conversion adhesive film of the present invention have simple preparation processes, can effectively reduce the ultraviolet attenuation of solar cells, and improve the solar light utilization efficiency and photoelectric conversion efficiency of the cells, and are suitable for various photovoltaic cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the embodiments are briefly introduced below.
[0020] Figure 1 This is a flow chart for the preparation of the Eu(TTA)3Bath complex in Example 1 of the present invention; Figure 2The SEM image and elemental scanning image of the Eu(TTA)3Bath complex in Example 1 of the present invention; Figure 3 FTIR spectrum of the Eu(TTA)3Bath complex in Example 1 of the present invention; Figure 4a 、 4b The excitation spectrum and emission spectrum of the Eu(TTA)3Phen complex in Comparative Example 1 and the Eu(TTA)3Bath complex in Example 1 are respectively; Figure 5 This is a diagram of the quantum yield of the Eu(TTA)3Bath complex in Example 1 of the present invention; Figure 6a 、 6b They are the excitation spectrum and emission spectrum of the Eu(TTA)3·2H2O complex in Comparative Example 2, respectively; Figure 7a 、 7b These are the UV absorption spectra of three ligands and three complexes respectively; Figure 8 This is a flow chart for preparing the Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film in Example 2 of the present invention; Figure 9 This is a physical picture of the Eu(TTA)3Bath@EVA photovoltaic light-conversion adhesive film in Example 2 of the present invention; Figure 10 This is the FTIR spectrum of the Eu(TTA)3Bath@EVA photovoltaic light conversion film in Example 2 of the present invention; Figure 11a 、 11b They are respectively the transmission spectra and absorption spectra of Eu(TTA)3Bath@EVA photovoltaic light conversion adhesive film at different volume fractions in Example 2 of the present invention; Figure 12a 、 12b They are respectively the excitation spectrum and emission spectrum of Eu(TTA)3Bath@EVA photovoltaic light conversion adhesive film at different volume fractions in Example 2 of the present invention; Figure 13 This is a quantum yield diagram of Eu(TTA)3Bath@PVB photovoltaic light conversion adhesive film and Eu(TTA)3Bath@EVA photovoltaic light conversion adhesive film in the present invention; Figure 14 The fluorescence spectrum test data of Eu(TTA)3Bath@EVA photovoltaic light conversion film in Example 2 of the present invention; Figure 15 These are the transmission spectra of the EVA photovoltaic light-conversion adhesive film and the Eu(TTA)3Bath@EVA photovoltaic light-conversion adhesive film in the present invention. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts should fall within the scope of protection of the present invention.
[0022] The present invention discloses a method for preparing a down-conversion material, comprising the following steps: Dissolve the trivalent europium salt compound in anhydrous ethanol and stir until completely dissolved to obtain solution A; Dissolve TTA in anhydrous ethanol and stir until completely dissolved to obtain solution B; Dissolve Bath in anhydrous ethanol and heat in a water bath with stirring until completely dissolved to obtain solution C; Solution A, solution B and solution C are mixed and stirred until fully reacted, and an alkaline solution is added to adjust the pH of the solution to pH <7. The solution is filtered and dried to obtain Eu(TTA)3Bath europium-based complex down-conversion material.
[0023] Among them, the trivalent europium salt compound can be one or more of EuCl3·6H2O, EuBr3·6H2O, Eu(NO3)3·6H2O, etc. Preferably, EuCl3·6H2O is used as an example for illustration in the present invention, and the preparation method and principle of other trivalent europium salt compounds are exactly the same as those of EuCl3·6H2O.
[0024] Furthermore, the preparation method of the down-conversion material comprises the following steps: Dissolve 0.5 mmol~2 mmol of EuCl3·6H2O in 5 mL~20 mL of anhydrous ethanol and stir at room temperature for 10 min~30 min until completely dissolved to obtain solution A; Dissolve 1 mmol~5 mmol of TTA in 5 mL~20 mL of anhydrous ethanol and stir at room temperature for 10 min~30 min until completely dissolved to obtain solution B; Dissolve 0.5 mmol~2 mmol of Bath in 5 mL~20 mL of anhydrous ethanol, heat in a water bath to 50℃~70℃, and stir for 10 min~30 min until completely dissolved to obtain solution C; After mixing solution A, solution B and solution C, stirring at room temperature for 0.5 h to 2 h until fully reacted, adding ammonia water to adjust the pH of the solution to pH = 6, filtering and drying, to obtain Eu(TTA)3Bath europium-based complex down-conversion material with a molecular structure as shown in Formula 1; [Formula 1] .
[0025] The present invention also discloses a method for preparing a photovoltaic light-converting adhesive film, comprising the following steps: Dissolve EVA powder in anhydrous ethanol and stir until completely dissolved to obtain solution D; The prepared Eu(TTA)3Bath europium-based complex down-conversion material was added to solution D and stirred until fully reacted to obtain solution E; Solution E is drop-coated on the photovoltaic glass, and then heated and cured. After ethanol is volatilized, it is cooled to form a Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film on the photovoltaic glass.
[0026] Preferably, the method for preparing the photovoltaic light-converting adhesive film comprises the following steps: Dissolve 0.2 g to 1 g of EVA powder in 5 mL to 20 mL of anhydrous ethanol and stir magnetically for 10 min to 30 min until completely dissolved to obtain solution D. Add 1.50 vol% of Eu(TTA)3Bath europium-based complex down-transfer material to solution D and stir at room temperature for 20 min to 40 min until the reaction is fully completed.
[0027] Solution E is drop-coated on the photovoltaic glass and then heated and cured at a temperature of 75°C to 95°C. After ethanol is volatilized, the solution is cooled to form a Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film on the photovoltaic glass.
[0028] The present invention will be further described below with reference to specific embodiments. Example 1
[0029] Ginseng Figure 1 As shown, the molecular structure of the Eu(TTA)3Bath europium-based complex down-conversion material in this embodiment is shown in Formula 1, and its preparation method includes the following steps: Dissolve 1 mmol of EuCl3·6H2O in 10 mL of anhydrous ethanol and continue stirring at room temperature for 20 min until it is completely dissolved; 3 mmol of TTA was dissolved in 10 mL of anhydrous ethanol and stirred at room temperature for 20 min; Dissolve 1 mmol of Bath in 10 mL of anhydrous ethanol and heat in a water bath at 60°C with constant stirring for 20 min; The three solutions were mixed, stirred at room temperature for 1 h, and finally ammonia water was added to adjust the pH to 6 to prepare the Eu(TTA)3Bath europium-based complex down-conversion material.
[0030] The SEM images and elemental scanning images of the Eu(TTA)3Bath europium-based complex down-conversion material prepared in this embodiment are shown in FIG. Figure 2 As shown, the FTIR spectrum is as follows Figure 3 As shown in Figure 2, the FTIR analysis of the Eu(TTA)3Bath complex shows a similar pattern, with the C=O vibration peak of the TTA ligand shifted to 1608 cm -1 Compared with the TTA before coordination, the CH bending vibration of Bath ligand is significantly red-shifted from 842 cm -1 and 747 cm -1 shifted to 784 cm-1 and 701 cm-1, respectively. -1 , and the characteristic peak of OH vibration of water molecules was not observed.
[0031] Comparative Example 1: The down-conversion material in this comparative example is a Eu(TTA)3Phen complex, and its preparation method comprises the following steps: About the preparation process of Eu(TTA)3Phen complex.
[0032] Dissolve 1 mmol of EuCl3·6H2O in 10 mL of anhydrous ethanol and stir at room temperature for 20 min until completely dissolved; 3 mmol of TTA and 1 mmol of Phen were dissolved in 10 mL of anhydrous ethanol, respectively, and stirred at room temperature for 20 min; The above solutions were mixed and stirred at room temperature for 1 h. Finally, ammonia water was added to adjust the pH to 6. After stirring for 1 h, a white precipitate was formed. The precipitate was washed three times with anhydrous ethanol and deionized water alternately. Finally, it was placed in an oven at 60°C and dried for 12 h to obtain the Eu(TTA)3Phen complex.
[0033] Ginseng Figure 4a 、 4b Shown are the excitation spectra and emission spectra of the Eu(TTA)3Phen complex in Comparative Example 1 and the Eu(TTA)3Bath complex in Example 1, respectively.
[0034] Ginseng Figure 4aThe excitation spectra shown in the figure show that both complexes exhibit broad-band absorption characteristics in the 250nm~380nm band. The absorption peak in the 280nm~320nm range corresponds to the π→π* electronic transition of the ligand TTA, while the weak absorption in the 320nm~400nm region is due to the Eu 3+ The 4f-4f characteristic transition of the complex is confirmed by the spectral feature, which confirms that the luminescence of the complex follows the ligand TTA-sensitized luminescence mechanism.
[0035] Ginseng Figure 4b The emission spectra shown are typical data of Eu 3+ The characteristic emission peak has a sharp emission peak at 613nm, which is mainly due to 5 D0→ 7 The other emission peaks at 580nm correspond to the electronic transition of F2 5 D0→ 7 F0, 592nm correspond 5 D0→ 7 F1, 652nm corresponding 5 D0→ 7 F3, 703nm correspond 5 D0→ 7 F4 prohibits electronic transitions.
[0036] Ginseng Figure 5 The figure shows the quantum yield of Eu(TTA)3Bath complex. It can be seen that Eu(TTA)3Bath complex shows a significant advantage, with a quantum yield value of 92.79%, which is doubled compared with 23.08% of Eu(TTA)3·2H2O and 78.44% of Eu(TTA)3Phen. This step-by-step improvement in quantum efficiency is due to a dual synergistic mechanism. On the one hand, the diphenyl extended conjugated system of the Bath ligand allows the triplet state T1 of the TTA ligand to react with the Eu(TTA)3·2H2O. 3+ of 5 The D0 excited state energy level is optimized to meet the critical conditions of Dexter energy transfer. On the other hand, the rigid planar structure of Bath forms a π-π stacking with TTA, which changes the coordination field symmetry through the steric effect and improves 5 D0→ 7 F2 electric dipole transition.
[0037] Comparative Example 2: The down-conversion material in this comparative example is a Eu(TTA)3·2H2O complex, and its preparation method comprises the following steps: First, 1 mmol of EuCl3·6H2O powder was weighed using an electronic scale and dissolved in 10 mL of anhydrous ethanol. Stirring was continued at room temperature for 20 min until it was completely dissolved. Then, 3 mmol of TTA was weighed and dissolved in 10 mL of anhydrous ethanol. After stirring at room temperature for 20 min until the powder was completely dissolved, the two solutions were mixed and stirred at room temperature for another 1 h. Finally, an appropriate amount of ammonia water was added to adjust the pH to 6. After stirring for 1 h, a white precipitate was formed. It was washed alternately with anhydrous ethanol and deionized water three times and dried in an oven at 60°C for 12 h to obtain the Eu(TTA)3·2H2O complex.
[0038] Ginseng Figure 6a 、 6b Shown are the excitation spectrum and emission spectrum of the Eu(TTA)3·2H2O complex in Comparative Example 2, respectively.
[0039] Ginseng Figure 6a The excitation spectrum shown in Figure 2 shows that the Eu(TTA)3·2H2O complex exhibits a broad absorption band in the ultraviolet region between 250 and 400 nm. The absorption in the range of 280 to 320 nm corresponds to the π→π* electronic transition of the TTA ligand. This spectral feature confirms that the luminescence of the complex follows a TTA-sensitized luminescence mechanism.
[0040] Ginseng Figure 6b The emission spectrum shown shows the typical Eu 3+ Characteristic emission peaks. Among them, the sharp peak at 580nm is attributed to 5 D0→ 7 F0 magnetic dipole transition, the 590nm doublet corresponds to 5 D0→ 7 F1 transition, the strongest emission peak at 613nm comes from 5 D0→ 7 F2 electric dipole transition, while the weak emission peak at 651nm is attributed to 5 D0→ 7 F3 jump.
[0041] It is worth noting that the emission peak at 613nm belongs to the same peak as that at 651nm. 5 D0→ 7 F2 transition system, this phenomenon originates from Eu 3 + The crystal field caused 7 F2 energy level Stark splitting. Under symmetry 7 The F2 energy level should split into sub-energy levels, but under the experimental conditions, only two main transition peaks at 613nm and 625nm were observed, which may be related to the specific symmetry of the complex and the transition selection rules.
[0042] Ginseng Figure 7aThe figure shows the UV absorption spectra of the three ligands. The TTA ligand exhibits a broad absorption spectrum from 200 nm to 400 nm, the Phen ligand exhibits a strong characteristic absorption peak at 225 nm, and the Bath ligand exhibits a stronger characteristic absorption at 275 nm, which is directly related to the enhanced π→π* transition caused by its extended π conjugated system.
[0043] Ginseng Figure 7b The UV absorption spectra of the three complexes are shown. The absorption of the Eu(TTA)3·2H2O complex decreases sharply after 300nm. In contrast, the Eu(TTA)3Phen and Eu(TTA)3Bath complexes exhibit broad absorption bands in the 300nm-410nm and 300nm-420nm ranges, and the absorption bands are red-shifted to 410nm and 420nm, respectively.
[0044] The improvement in the absorption performance of the ligand and the complex is due to the cooperative ligand eliminating the non-radiative relaxation caused by the coordination of water molecules, which improves the radiation efficiency. In addition, the diphenyl structure of Bath increases the molecular orbital overlap, thereby enhancing the light absorption ability in the ultraviolet band. Example 2
[0045] Ginseng Figure 8 As shown, the preparation method of Eu(TTA)3Bath@EVA photovoltaic light conversion adhesive film in this embodiment includes the following steps: First, the Eu(TTA)3Bath complex precursor solution was prepared according to the preparation method in Example 1; Then, a certain mass of EVA particles was weighed, dissolved in 10 mL of dichloromethane, and magnetically stirred at room temperature for 30 min until completely dissolved into a transparent solution; Eu(TTA)3Bath complex precursor solutions with different volume fractions were added to EVA in dichloromethane and stirred at room temperature for 30 min to allow the two to be fully mixed. Finally, 1 mL of the mixed solution was drop-coated on a 3 cm × 3 cm photovoltaic patterned glass. The sample was then placed on a hot plate at 85°C for curing. After cooling, the Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film glass was obtained.
[0046] Ginseng Figure 9 As shown in (a), the prepared Eu(TTA)3Bath@EVA photovoltaic light conversion film maintains high transparency under natural light. Figure 9 As shown in (b), it exhibits characteristic red light emission under 365nm ultraviolet excitation.
[0047] Through SEM characterization, Figure 9(c) shows that the pure PVB film exhibits a typical amorphous structure on its surface, while (d) indicates that the Eu(TTA)3Bath complex in the Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film is relatively uniformly dispersed, with no significant phase separation or agglomeration. This confirms the feasibility of the process of blending the Eu(TTA)3Bath precursor ethanol solution with the PVB ethanol solution, and that the resulting film can maintain the fluorescence properties of the down-conversion material.
[0048] Ginseng Figure 10 The FTIR spectrum of Eu(TTA)3Bath@EVA photovoltaic light conversion film is shown. According to the spectrum, the -OH vibration absorption peak is between 3200 and 3500 cm -1 The hydroxyl stretching vibration peak of PVB shifted from 3445 cm -1 Redshift to 3327 cm -1 , which is consistent with the characteristic shift of hydrogen bond formation, indicating that hydrogen bonding is formed between the hydroxyl groups in PVB and the europium complex. In addition, the carbonyl vibration peak in the acetal group shifts from 1732 cm -1 Shift to 1718 cm -1 , indicating that the β-diketone group of the TTA ligand forms an intermolecular dipole interaction with PVB. The carbonyl C=O at 1612 cm -1 The characteristic absorption peak is shifted, mainly due to the influence of hydrogen bonding on the acetal group in PVB. This hydrogen bonding can increase the structural stability of the europium complex and form a protective mechanism. In addition, at 580 cm -1 A characteristic peak appears at , which is attributed to the symmetrical stretching vibration of the Eu-O bond. The position of this vibration peak is almost consistent with that of the pure phase Eu(TTA)3Bath complex sample, indicating that the microenvironmental constraint effect formed by the PVB matrix through the hydrogen bond network enables the original complex to maintain its own structure, proving that the structural integrity of the complex Eu(TTA)3Bath complex is maintained during the composite process.
[0049] Figure 11a 、 11b , 12a, and 12b show the transmission spectrum, absorption spectrum, excitation spectrum, and emission spectrum of Eu(TTA)3Bath@EVA photovoltaic light conversion adhesive film at different volume fractions, where the volume fractions are shown in the following table:
[0050] Figure 11aThe transmission spectra show that in the ultraviolet range of 280 nm to 400 nm, the transmittance of the film sample decreases significantly with increasing Eu(TTA)3Bath doping ratio. This is related to the characteristic absorption of the ligands TTA and Bath in the Eu(TTA)3Bath complex in the ultraviolet range. Furthermore, increasing the proportion of the Eu(TTA)3Bath complex leads to a slight decrease in transmittance in the visible light range of 400 nm to 800 nm. This is due to the complex's tendency to agglomerate, which affects transmittance.
[0051] Figure 11b The absorption spectrum shows that the absorption intensity in the ultraviolet band increases with the increase of doping concentration, which is attributed to the characteristic absorption of ligands TTA and Bath in the Eu(TTA)3Bath complex in the ultraviolet band, which is consistent with the above-mentioned transmittance change trend.
[0052] Figure 12a The excitation spectrum of the Eu(TTA)3Bath@EVA photovoltaic light-conversion adhesive film shows strong absorption in the 250nm to 400nm UV range, with the absorption intensity increasing with increasing complex content. This is similar to the excitation spectrum of the Eu(TTA)3Bath complex and is attributed to the absorption of the TTA and Bath ligands in the complex.
[0053] Figure 12b The emission spectrum of Eu(TTA)3Bath@EVA photovoltaic light conversion film shows that it has a characteristic emission peak at 613nm, which belongs to Eu 3+ of 5 D0→ 7 The characteristic peak of F2 energy level transition. It can be seen that with the increase of Eu(TTA)3Bath content, the luminescence intensity shows a gradually increasing trend.
[0054] It can be seen from both the excitation spectrum and the emission spectrum that Eu(TTA)3Bath doped into the EVA film still maintains its original fluorescence characteristics. With the increase of the doping amount, the fluorescence intensity increases. Preferably, when the volume fraction of the Eu(TTA)3Bath complex is 1vol%~2vol%, the effect is best.
[0055] Ginseng Figure 13The quantum yields of two photovoltaic light-conversion adhesive films are shown. The quantum yield of the Eu(TTA)3Bath@PVB photovoltaic light-conversion adhesive film is only 64.47%, while the quantum yield of the Eu(TTA)3Bath@EVA photovoltaic light-conversion adhesive film maintains the original quantum yield of the complex at 92.79%. This is primarily due to the differences in the molecular structures of the two polymers. EVA's molecular chains easily form a flexible cross-linked network, which crosslinks and grafts with the complex, inhibiting particle aggregation and preventing the concentration quenching effect caused by particle agglomeration, thereby maintaining the quantum yield. PVB, on the other hand, has a more rigid molecular chain. Its acetal groups and long-chain alkyl groups make it highly hydrophobic, resulting in poor compatibility with polar ligands. This easily triggers local aggregation of the complex, leading to concentration quenching and a reduction in quantum yield.
[0056] The volume resistivity and cross-linking degree of Eu(TTA)3Bath@EVA photovoltaic light conversion film were tested, and the results are shown in the following table:
[0057] It can be seen that both the degree of cross-linking and the volume resistivity meet industry standards. The degree of cross-linking determines the tear resistance, adhesion, and weather resistance of photovoltaic modules, while the volume resistivity directly affects the photovoltaic module's resistance to electrical corrosion in humid environments.
[0058] Ginseng Figure 14 This is the fluorescence spectrum test data of Eu(TTA)3Bath@EVA photovoltaic light conversion film in this embodiment.
[0059] Figure 14 (a) is a photo of the appearance of the photovoltaic light conversion film under natural light. Figure 14 (b) is a photo of the appearance of the light-converting film emitting red light under ultraviolet light (UV=365nm), which shows that the prepared Eu(TTA)3Bath@EVA photovoltaic light-converting film can convert ultraviolet light into red light and has light conversion function.
[0060] Figure 14 (c) shows the excitation spectrum. The Eu(TTA)3Bath@EVA photovoltaic light-conversion adhesive film exhibits a strong spectral response across the entire UV range, absorbing UV light. This is attributed to the absorption of the TTA and Bath ligands in the complex. It is worth noting that the excitation spectrum here differs slightly from that of the previously prepared Eu(TTA)3Bath complex. This is due to chemical side reactions caused by the addition of various additives during the preparation of the photoresist film, resulting in slight spectral variations.
[0061] Figure 14As shown in (d), the emission characteristic peak of Eu(TTA)3Bath@EVA photovoltaic light conversion film is exactly the same as that of Eu(TTA)3Bath complex, and its emission spectrum still shows the main emission peak at 613nm, which is also attributed to Eu 3+ Characteristics of ions 5 D0→ 7 F2 electric dipole transition mechanism.
[0062] Figure 15 The transmission spectra of EVA photovoltaic light-conversion adhesive film and Eu(TTA)3Bath@EVA photovoltaic light-conversion adhesive film are shown. In the 280nm-400nm UV band, the prepared photovoltaic light-conversion adhesive film has an average transmittance of approximately 10.98%, meeting the UV protection requirements of solar cell modules. In the visible light band of 400nm-800nm, its average transmittance reaches 90.89%, which is basically the same as that of ordinary EVA adhesive film. This shows that the addition of the Eu(TTA)3Bath complex to the transfer luminescent material has no effect on the transmittance in the visible light band, and the two have excellent compatibility and are compatible with current industrial processes.
[0063] EVA photovoltaic light conversion adhesive film and Eu(TTA)3Bath@EVA photovoltaic light conversion adhesive film were applied to HJT battery modules respectively. The average electrical performance parameters of the two film HJT battery modules are shown in the following table:
[0064] The results show that the power of the HJT solar cell test piece containing Eu(TTA)3Bath@EVA photovoltaic light conversion film is 0.16 W higher than that of the HJT small component containing only ordinary EVA film in the control group. sc The improvement of 0.065 A is due to the fact that the down-shifted luminescent material absorbs ultraviolet light and re-emits visible red light, increasing the efficient utilization of photons and thus improving the short-circuit current of the battery.
[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.
Claims
1. A method for preparing a down-conversion material, characterized in that: The preparation method comprises the following steps: Dissolve the trivalent europium salt compound in anhydrous ethanol and stir until completely dissolved to obtain solution A; Dissolve TTA in anhydrous ethanol and stir until completely dissolved to obtain solution B; Dissolve Bath in anhydrous ethanol and heat in a water bath with stirring until completely dissolved to obtain solution C; Solution A, solution B and solution C are mixed and stirred until fully reacted, and an alkaline solution is added to adjust the pH of the solution to pH <7. The solution is filtered and dried to obtain Eu(TTA)3Bath europium-based complex down-conversion material.
2. The method for preparing a down-conversion material according to claim 1, wherein: The trivalent europium salt compound includes at least one of EuCl3·6H2O, EuBr3·6H2O, and Eu(NO3)3·6H2O.
3. The method for preparing a down-conversion material according to claim 1, wherein: The preparation of the solution A comprises: Dissolve 0.5 mmol~2 mmol of trivalent europium salt compound in 5 mL~20 mL of anhydrous ethanol and stir at room temperature for 10 min~30 min until completely dissolved.
4. The method for preparing a down-conversion material according to claim 1, wherein: The preparation of the solution B comprises: Dissolve 1 mmol~5 mmol of TTA in 5 mL~20 mL of anhydrous ethanol and stir at room temperature for 10 min~30 min until completely dissolved.
5. The method for preparing a down-conversion material according to claim 1, wherein: The preparation of the solution C comprises: Dissolve 0.5 mmol~2 mmol of Bath in 5 mL~20 mL of anhydrous ethanol, heat in a water bath to 50℃~70℃, and stir for 10 min~30 min until completely dissolved.
6. The method for preparing a down-conversion material according to claim 1, wherein: After mixing solution A, solution B and solution C, stirring at room temperature for 0.5 h to 2 h until fully reacted, adding ammonia water to adjust the pH of the solution to pH = 6, filtering and drying, to obtain Eu(TTA)3Bath europium-based complex down-conversion material with a molecular structure as shown in Formula 1; [Formula 1] 。 7. A method for preparing a photovoltaic light-converting adhesive film, characterized in that: The preparation method comprises the following steps: Dissolve EVA powder in anhydrous ethanol and stir until completely dissolved to obtain solution D; Adding the Eu(TTA)3Bath europium-based complex down-conversion material prepared according to any one of claims 1 to 6 to solution D, stirring until fully reacted, to obtain solution E; Solution E is drop-coated on the photovoltaic glass, and then heated and cured. After ethanol is volatilized, it is cooled to form a Eu(TTA)3Bath@EVA photovoltaic light-converting adhesive film on the photovoltaic glass.
8. The method for preparing the photovoltaic light-converting adhesive film according to claim 7, characterized in that: The preparation of the solution D comprises: Dissolve 0.2 g~1 g of EVA powder in 5 mL~20 mL of anhydrous ethanol and stir magnetically for 10 min~30 min until completely dissolved.
9. The method for preparing the photovoltaic light-converting adhesive film according to claim 7, characterized in that: The preparation of the solution D comprises: Add 1 vol% to 2 vol% of Eu(TTA)3Bath europium-based complex down-transfer material to solution D and stir at room temperature for 20 min to 40 min until the reaction is fully completed.
10. The method for preparing the photovoltaic light-converting adhesive film according to claim 7, characterized in that: After the solution E is drop-coated on the photovoltaic glass, it is heated and cured at a temperature of 75° C. to 95° C.
11. A photovoltaic module, characterized in that: The photovoltaic module includes photovoltaic glass and a photovoltaic light-converting adhesive film located on the photovoltaic glass, and the photovoltaic light-converting adhesive film is prepared by the preparation method described in any one of claims 7 to 10.
Citation Information
Cited By
Photovoltaic light conversion adhesive film as well as preparation method and application thereof
CN120737800A
Silicon quantum dot with core-shell structure as well as preparation method and application of silicon quantum dot
CN121674058A